Angiotensin II receptor 1 controls profibrotic Wnt/β-catenin signalling in experimental autoimmune myocarditis. Issue 2 (8th February 2021) - Czepiel, Marcin; Diviani, Dario; Jaźwa-Kusior, Agnieszka; Tkacz, Karolina; Rolski, Filip; Smolenski, Ryszard T; Siedlar, Maciej; Eriksson, Urs; Kania, Gabriela; Błyszczuk, Przemysław
Abstract: Aims: Angiotensin (Ang) II signalling has been suggested to promote cardiac fibrosis in inflammatory heart diseases; however, the underlying mechanisms remain obscure. Using Agtr1a -/- mice with genetic deletion of angiotensin receptor type 1 (ATR1) and the experimental autoimmune myocarditis (EAM) model, we aimed to elucidate the role of Ang II-ATR1 pathway in development of heart-specific autoimmunity and post-inflammatory fibrosis. Methods and results: EAM was induced in wild-type (WT) and Agtr1a -/- mice by subcutaneous injections with alpha myosin heavy chain peptide emulsified in complete Freund's adjuvant. Agtr1a -/- mice developed myocarditis to a similar extent as WT controls at day 21 but showed reduced fibrosis and better systolic function at day 40. Crisscross bone marrow chimaera experiments proved that ATR1 signalling in the bone marrow compartment was critical for cardiac fibrosis. Heart infiltrating, bone-marrow-derived cells produced Ang II, but lack of ATR1 in these cells reduced transforming growth factor beta (TGF-β)-mediated fibrotic responses. At the molecular level, Agtr1a -/- heart-inflammatory cells showed impaired TGF-β-mediated phosphorylation of Smad2 and TAK1. In WT cells, TGF-β induced formation of RhoA-GTP and RhoA-A-kinase anchoring protein-Lbc (AKAP-Lbc) complex. In Agtr1a - /- cells, stabilization of RhoA-GTP and interaction of RhoA with AKAP-Lbc were largely impaired. Furthermore, in contrast to WT cells, Agtr1a - /- cells stimulated with TGF-β failed to activate canonical Wnt pathway indicated by suppressed activity of glycogen synthase kinase-3 (GSK-3)β and nuclear β-catenin translocation and showed reduced expression of Wnts . In line with these in vitro findings, β-catenin was detected in inflammatory regions of hearts of WT, but not Agtr1a - /- mice and expression of canonical Wnt1 and Wnt10b were lower in Agtr1a - /- hearts. Conclusion: Ang II-ATR1 signalling is critical for development of post-inflammatory fibrotic remodelling and dilated cardiomyopathy. Our data underpin the importance of Ang II-ATR1 in effective TGF-β downstream signalling response including activation of profibrotic Wnt/β-catenin pathway. Graphical Abstract: